2019
DOI: 10.4049/jimmunol.202.supp.189.8
|View full text |Cite
|
Sign up to set email alerts
|

STAT4 programs CD103− tissue-resident memory cells during infection

Abstract: Tissue-resident memory (Trm) CD8+ T cells represent a distinct population of memory T cells that are maintained independently of the circulation and are positioned to respond rapidly to reinfection of the tissue. Using the bacterial pathogen Yersinia pseudotuberculosis (Yptb), we identified two distinct intestinal CD8+ Trm populations that are differentiated by their expression of the integrin CD103. Proximity of T cells to areas of inflammation within the intestinal tissue regulated Trm differentiation, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Inhibition of AKT signalling has been shown to promote central memory responses by increasing nuclear accumulation of FOXO1 [ 39 ]. It is also well-established that STAT3 and STAT4 play specific function in the formation of T cell memory subsets in response to infections [ 16 , 40 ]. To further ascertain the influence of BBR treatment on AKT-FOXO1 axis, we repeated the ex vivo T cell stimulation experiment in the presence of AKTi and BBR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of AKT signalling has been shown to promote central memory responses by increasing nuclear accumulation of FOXO1 [ 39 ]. It is also well-established that STAT3 and STAT4 play specific function in the formation of T cell memory subsets in response to infections [ 16 , 40 ]. To further ascertain the influence of BBR treatment on AKT-FOXO1 axis, we repeated the ex vivo T cell stimulation experiment in the presence of AKTi and BBR.…”
Section: Resultsmentioning
confidence: 99%
“…Previously it has been reported that the T RM cells have a definite cytokine profile (TGFβ, IL15, Type I IFN, IL12) as well as T RM- specific transcription factors such as Runx3, Hobit, Blimp1etc [ 59 ] that distinguish them from other immune cell populations and enriching selective and protective tissue specific immunity. Apart from this, certain studies have ascertained the critical role of STAT4 in regulating T RM differentiation and persistence in achieving tissue-specific immunity against infections [ 40 ]. Ex vivo BBR treatment elicited the expansion of T cell memory pool by modulating vital interconnected immune molecules such as AKT, FOXO-1, STAT-3, STAT-4, BLIMP-1 as well as NFκB.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports suggest that JAK/STAT signaling pathways play an important role in T cell memory responses ( 40 , 41 ). STAT3 induces central memory T cells ( 42 , 43 ), while STAT4 plays a critical role in the long-term T cell memory responses ( 44 ). Interestingly, WA treatment significantly enriched the percentages of pSTAT4- and pSTAT3-expressing CD4 + and CD8 + subsets ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that STAT signaling can orchestrate the establishment and maintenance of memory cell populations in response to infections ( 43 ). It is known that STAT3 plays a vital role in the production and continuation of memory cell populations ( 43 , 59 ) and that STAT4 is majorly involved at the site of infection and in stimulating tissue-resident memory responses ( 44 ). To evaluate the anticipated role of immunological signaling in the establishment of protective memory cell populations, we assessed the status of signal transducers in response to WA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these signals cooperate in IFN-g induction of CD4 + and CD8 + T cells. Type I IFNs, IL-12 and STAT4 have been shown to be important for the development of CD69 + CD103 -Trm cells in various tissues, including the liver [396,548] . IL-12Rb -/-or STAT4 -/-C57 strains also exhibit less CD69 + CD103 -Trm cells following Yersinia infection but had no change in CD69 + CD103 + Trm cells.…”
Section: Discussionmentioning
confidence: 99%